(untitled) (Ekonomski vjesnik/Econviews - Review of Contemporary Business, Entrepreneurship and Economic Issues, 2021)
Purpose: The definition of the digital economy changes depending on the time period the definition comes from and the prevailing technology of that period, from the Internet to advanced robotics or artificial intelligence. The purpose of this paper is to identify the core terms, give a definition of the digital economy, identify the most influential journals, authors and documents that deal with the topic and provide an overview of the development of academic literature over the years. Methodology: 293 documents related to the term “digital economy” were retrieved from the Scopus database. By using citation, co-citation, bibliographic coupling analysis and co-occurrence of the keywords, this paper identifies a list of the most influential journals, authors and documents in the field of digital economy. The analysis was conducted by using the VOSviewer tool. An in-depth analysis of the documents was used to prepare an overview of the definitions of the digital economy. Results: The research proves inconsistency of the definition and context of the digital economy as well as a significant impact of a small number of authors and journals in the area under study. Keyword analysis shows that the term digital economy is related not to macroeconomic terms but to more specific industrial terms. Conclusion: Guidelines are provided for future scientific research to fill the gaps in the definition and scope of the digital economy.